The Listening Network and Cochlear Implant Benefits in Hearing-Impaired Adults - James, Chris J.; Graham, Petra L.; Betances Reinoso, Frank A.; Breuning, Silvia N.; Durko, Marcin; Huarte Irujo, Alicia; Royo López, Juan; Müller, Lida; Perenyi, Adam; Jaramillo Saffon, Rafael; Salinas Garcia, Sandra; Schüssler, Mark; et al. (Frontiers in Aging Neuroscience, 2021)
Older adults with mild or no hearing loss make more errors and expend more effort listening to speech. Cochlear implants (CI) restore hearing to deaf patients but with limited fidelity. We hypothesized that patient-reported hearing and health-related quality of life in CI patients may similarly vary according to age. Speech Spatial Qualities (SSQ) of hearing scale and Health Utilities Index Mark III (HUI) questionnaires were administered to 543 unilaterally implanted adults across Europe, South Africa and South America. Data were acquired prior to surgery and at 1, 2 and 3 years. Data were analyzed using linear mixed models with visit, age group (18-34, 35-44, 45-54, 55-64 and 65+) and side of implant as main factors and adjusted for other covariates. Tinnitus and dizziness prevalence did not vary with age, but older groups had more preoperative hearing. Preoperatively and postoperatively SSQ scores were significantly higher (∆0.75-0.82) for those aged <45 compared with those 55+. However, gains in SSQ scores were equivalent across age groups, although postoperative SSQ scores were higher in right-ear implanted subjects. All age groups benefitted equally in terms of HUI gain (0.18), with no decrease in scores with age. Overall, younger adults appeared to cope better with degraded hearing prior to and after CI, leading to better subjective hearing performance.